Small Intestinal Tumours. (17th November 2013) - Kopáčová, Marcela; Rejchrt, Stanislav; Bureš, Jan; Tachecí, Ilja
Abstract : Objective . Balloon enteroscopy (BE) and capsule enteroscopy (CE) are enteroscopy methods that allow examination and treatment of the small bowel. Before the CE and BE era, the small intestine was difficult to access for investigation. Small intestinal tumours are infrequent conditions, but about half of them are malignant. Materials and Methods . A total of 303 BEs were performed in 179 patients. Oral insertion was performed in 240 and anal in 63 BEs. Indications for the procedure in our patients with small bowel tumours were anaemia and/or bleeding, obstruction, suspicion of carcinoid tumour, or suspicion of Peutz-Jeghers syndrome. Results . In 50 of our 179 patients (28%), we diagnosed some small intestinal tumours: hamartomas in Peutz-Jeghers syndrome in 16 patients, adenocarcinoma in 7, lymphoma in 6, carcinoid tumour in 4, melanoma and stromal tumour in 3, adenoma, lipoma, and inflammatory polyps in 2, and granular cell tumour, cavernous lymphangioma, fibrolipoma, Cronkhite-Canada polyps, and metastatic involvement in individual cases. Conclusion . BE facilitates exploration and treatment of the small intestine. The procedure is generally safe and useful. BE and CE are essential modalities for the management of small intestinal diseases.